Application of Young Coconut Water and “Kascing” Fertilizer to Red Palm Seed Germination - Zuhro, Fatimatuz; Hasanah, Hasni Ummul; Sukadi, Sukadi (Jurnal ILMU DASAR, 2017)
Redpalm isornamentplantwhichpotentiallytobecultured.Thescarcityofredpalmmadeithashighmarket value and need to be preserved. However, the germination growth of red palm is slower than other kinds of palm, so the best way to germinate the red palm seed is needed. The aim of this research is to determine the effect of apliccation some young coconut water concentration and kascing fertilizer to red palm seed germination. The research used factorial completely randomized design with 5 replication, the first factor is young coconut water concentration (0%, 25%, 50%, 75%, and 100%) and the second factor is germination media (steril sand and kascing fertilizer). Variables measured were live germination percentage, speed germination rate, radicula length, and plumula height. Results of this study showed that the best germination media is steril sand and 0% concentration of young coconut water.